Studi Komparasi Penyelesaian Wasiat Wajibah di Indonesia dan Malaysia - Susanti, Neneng Desi; Akbarizan, Akbarizan (JAWI : Journal of Ahkam Wa Iqtishad, 2023)
A will is a legal document that outlines how a person's assets will be distributed after their death.   In some countries, the distribution of assets is regulated by law and not solely based on the wishes of the deceased. This is known as a mandatory will, which limits the amount that can be given to certain parties to no more than one-third of the total assets. Indonesia and Malaysia are countries that regulate the matter of mandatory wills. The purpose of this journal is to identify the similarities and differences in the provisions of mandatory wills in Indonesia and Malaysia, to determine the Islamic legal basis for mandatory wills, and to examine the development of mandatory wills in both countries.